(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
In Ayurvedic classics, Kasa Roga is identified as a disorder of the Praṇavaha Srotas and is categorized according to Doṣa predominance. Among its variants, Kaphaja Kasa is the most commonly observed during Balyavastha (childhood), a stage inherently dominated by Kapha Doṣa. It manifests as a productive cough with thick sputum, chest heaviness, nasal discharge, anorexia, and mild chest pain. Ayurvedic texts recommend Kasa-Shamana (cough-relieving) formulations for such conditions, with Kashyapokt Pipaliadileha and Pushkaradileha being two classical preparations indicated for Kaphaja Kasa. Objective: To evaluate and compare the clinical efficacy of Kashyapokt Pipaliadileha and Pushkaradileha in the management of Kaphaja Kasa in children. Materials and Methods: A randomized controlled clinical study was conducted on sixty children aged 2–5 years diagnosed with Kaphaja Kasa. Group A received Kashyapokt Pipaliadileha (5gm twice daily with honey), and Group B received Pushkaradileha (5gm twice daily with honey) for fifteen days. Assessment was made based on subjective and objective parameters such as cough frequency, sputum quantity, chest heaviness, and adventitious lung sounds. Data were statistically analyzed using SPSS software. Results: Both formulations produced significant symptomatic relief; however, Kashyapokt Pushkaradileha showed superior improvement in reducing sputum, and chest crepitations etc (p<0.05). Conclusion: Kashyapokt Pushkaradileha proved more efficacious than Pippaliadileha in managing Kaphaja Kasa in children. Puṣkaradileha effectively disrupts the Samprapti of Kaphaja Kasa by alleviating Kapha Sanga, normalizing Vata Gati, and improving Agni Bala and Pranavaha Srotas function, and Tridosha shamaka properties effectively pacify Kapha Dosha, supporting its role as a safe and potent Ayurvedic formulation for pediatric respiratory disorders.